THE EFFECT OF PREOPERATIVE EDUCATION ON SELF EFFICACY AND BEHAVIOR OF POST OPERATIVE PATIENTS OF LOWER EXTREMITY FRACTURES - Padma Sekar Ayu Putri Prahasta; Sri Lestari Ramadhani Nasution; Juwita Hotmida Sitorus (Jambura Journal of Health Sciences and Research, 2022)
Preoperative education is a form of education given before surgery patients, education contains things that patients will do after surgery. Preoperative education can improve self-efficacy and patient behavior. Objectives: To investigate whether there is an effect of preoperative education on self-efficacy and behavior in lower extremity fracture patients; Methods: This study used a quantitative method with a Quasi Experimental design with a pretest and posttest control group approach. The sample used was 52 respondents who were diagnosed as lower extremity fractures. Respondents were divided into 2 groups: intervention (provided education in the form of videos) and control (given verbal education); Results: after the study was completed and the score was calculated, there was an increase in the two control and intervention groups in the self-efficacy questionnaire scores but there was a significant increase in self-efficacy and exercise behavior in the intervention group who were given preoperative education via video for 15 minutes, namely 53.84 % self efficacy scores and 21 behavioral scores; Conclusion: In this study it was found that preoperative education is important in patient care, education provided through video is proven to be more effective in increasing self-efficacy and improving postoperative exercise behavior in lower extremity fracture patients compared to preoperative education given verbally.